The Influence of Financial Performance and Underwriter Reputation on Annual Return - Jaunanda, Meiliana; Angelia, Frieska (UNKLAB Business School, 2024)
This study examines the effect of profitability, liquidity, financial leverage, and the underwriter's reputation on the underpricing of Initial Public Offering (IPO) shares. Samples were taken from companies that conducted an IPO on the Indonesia Stock Exchange from 2018 to 2021 using a purposive sampling method, resulting in sample data from 62 companies. Data on underpricing were measured using initial return, profitability was measured by return on equity (ROE), liquidity was measured using the current ratio (CR), financial leverage was measured using the debt-to-equity ratio (DER), and underwriter's reputation was measured using the top 10 in terms of the 20 most active brokerage houses monthly in total trading frequency during the study period. The results of this study indicate that profitability (ROE) and underwriter reputation (RU) have a negative and significant effect on underpricing, while liquidity (CR) and financial leverage (DER) have a negative and insignificant effect on underpricing.